2021
DOI: 10.1192/bjb.2021.122
|View full text |Cite
|
Sign up to set email alerts
|

Sleep: the neglected life factor in adults with intellectual disabilities

Abstract: Sleep is vital for our physical and mental health. Studies have shown that there is a high prevalence of sleep disorders and sleep difficulties amongst adults with intellectual disabilities. Despite this, sleep is often overlooked or its disorders are considered to be difficult to treat in adults with intellectual disabilities. There is a significant amount of research and guidance on management of sleep disorders in the general population. However, the evidence base for sleep disorders in adults with intellec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Despite a recent significant expansion of our understanding of sleep and sleep disorders, our knowledge of how these advancements pertain to adults with ID remains limited [3]. Sleep disorders in adults with ID are often referred in the literature under different terminologies, such as behavioural sleep problems, which may encompass any sleep disorder from insomnia to narcolepsy [4].…”
Section: Current Evidence Base On Sleep and Sleep Disorders In People...mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a recent significant expansion of our understanding of sleep and sleep disorders, our knowledge of how these advancements pertain to adults with ID remains limited [3]. Sleep disorders in adults with ID are often referred in the literature under different terminologies, such as behavioural sleep problems, which may encompass any sleep disorder from insomnia to narcolepsy [4].…”
Section: Current Evidence Base On Sleep and Sleep Disorders In People...mentioning
confidence: 99%
“…We have previously proposed one approach for the screening, assessment and treatment of sleep disorders in adults with ID (Table 2 and Fig. 1) [3,31]. In our experience, treatment plans frequently require a holistic multi-modal approach, which may in part be based on existing standard adult sleep medicine treatment guidelines.…”
Section: Homeostaticmentioning
confidence: 99%
“…Further, the extent of sleep alterations seems to be related to the severity of learning disability 4. Despite the higher prevalence compared with the general population and the additional impairment in daily functioning, an in-depth understanding of the conceptualisation and treatment of sleep difficulties among this population is still lacking 5…”
Section: Commentarymentioning
confidence: 99%
“…Two recent literature reviews showed that non-pharmacological interventions (e.g. activity scheduling, stimulus control, cognitive-behaviour therapy, relaxation and sleep hygiene) focusing on improving the sleep-wake rhythm and/or mood are not yet evidence based for people with IDs (Priday et al 2017;Shanahan et al 2019;Korb et al 2023).…”
Section: Introductionmentioning
confidence: 99%